PENGARUH PENDIDIKAN ISLAM WANITA KARIR TERHADAP KECERDASAN SPIRITUAL EMOSIONAL ANAK USIA REMAJA - Ufit Fitriyani; Muslihudin; Akhmad Affandi (CV. ADIBA ASIHA AMIRA, 2025)
This research aims to find out information about career women's Islamic education, children's spiritual intelligence, children's emotional intelligence and also to find out how much influence career women's Islamic education has on children's emotional spiritual intelligence at IAIN Sheikh Nurjati Cirebon. In this study, there are several problem findings including: children become quiet and closed because of the lack of career parents, forgetting time when playing games, sometimes resisting when parents talk. The researcher used quantitative methods by collecting data with a questionnaire, then analysed using simple regression. Based on the results of the analysis, the Islamic education of women who work as career women is in the good category with a magnitude of 89.8%. Children's spiritual intelligence is in the good category at 81.2%. Children's emotional intelligence is in the good category at 82.3%. There is an influence between the Islamic education of career women and children's spiritual intelligence with a correlation of 29.3%, which shows a low correlation and the influence between career women's Islamic education and children's emotional intelligence with a correlation that reaches 34.6%, which shows a low correlation.